Transferrin levels in antenatal women - Sherin Stephen; P Samatha (International Journal of Medical Research and Review, 2016)
Introduction: During pregnancy, hemodilution leads to reduced hemoglobin, iron and ferritin concentration with increase in total iron binding capacity. Iron deficiency anemia is an important risk factor in pregnancy, attributing to 16% of all maternal deaths in India. Transferrin saturation is considered as the best marker of the iron supply for erythropoiesis . The aim of the study is to evaluate the levels of transferrin in antenatal women as a risk factor for iron deficiency anemia. The specific objectives are to find out comparison and correlation of the parameters used in the study.Methods: The present study group consists of 100 patients and 25 controls. Serum transferrin, total iron finding capacity and hemoglobin levels were investigated. Serum iron binding capacity and transferring levels were estimated by Ferrozine methods and hemoglobin by Cyanmethphotometric method.Results: The mean levels of transferrin in the patients in first trimester were 2.51+ 0.074 g/L, second trimester 2.87+ 0.058 g/L and 2.16 + 0.72 g/L in controls, which was statistically significant. The levels of total iron binding capacity in patients in the three trimesters were 358.36 + 10.73 μg/dl, 409.53 + 7.91 μg /dl and 471.57 + 12.10 μg /dl when compared to 308.48 + 10.09 μg /dl in controls and was statistically significant.Conclusion: The hemoglobin levels decreased significantly during each trimester than controls along with significant P values in second and third trimesters. Hence estimating the level of transferrin can be used as a marker for assessing iron deficiency anemia in pregnancy.